Colours Convey Lanna Identity in Lamphun and Chiang Mai Area - Karuna Raksawin (2018)
© Published under licence by IOP Publishing Ltd. Colour control is a specific tool to identify local environment. Especially in the historic area or conservation area, to promote colour control is very necessary. Therefore, there are many standards of colour to control such as Munsell, colour name, and L∗a∗b∗. This research is aimed to analyze the appropriate colour control by using a Munsell standard colour which is suitable to visual perception. The study area is scoped in northern region of Lanna culture in Thailand which nowadays used names of colours to control. Chiang Mai and Lamphun are selected to be case study because they are in a center of Lanna Empire of Thailand and have many historic significant things such as city wall, temple, monastery, palace, and city moat. The mainly procedure conducts in this article is based on the analysis of material colour. The study chose local natural materials which are used in the historic significant things. Earthen clay tile, wooden roof tile, burnt clay brick, laterites, hard wood, bamboo, silver, and gold are evaluated. The procedure used the DIC application of android processor on smart phone. This application has a conversion data to switch a colour value from pick-up point in photo to many colour values such as RGB, CMYK which Munsell value is included. The photos were taken within the historic area of Chiang Mai and Lamphun by random. The result can scope a range of colours of Munsell standard of natural colour (N), red (R), yellow (Y), and yellow-red (YR). A natural colour (N) can be suggested a range 1.0-9.0 (N 1.0-9.0). Red can be ranged the value between 3.0-7.0 and chroma between 3.0-9.0 (R 3.0-7.0/3.0-9.0). Yellow can be ranged the value between 6.0-9.0 and chroma between 4.0-12.0 (Y 6.0-9.0/4.0-12.0). Yellow-red can be ranged the value between 2.0-8.0 and chroma between 2.0-11.0 (YR 2.0-8.0/2.0-11.0). The results can be revealed a process of colour analysis of historic colour control and may offer to be an ordinance in further.